The Reproductive Performance of Breeder Cocks Fed Cottonseed Cake-based Diets - Adeyemo, G.O.; Longe, O.G.; Adejumo, D.O. (International Journal of Poultry Science, 2007)
Histology of the testes of breeder cocks fed replacement levels of 0, 25, 50, 75, or 100% of cottonseed meal (CSM) for soybean meal (SBM) in five different breeder diets for fifteen weeks were investigated in a completely randomized design. Chemical analyses were carried out to determine the crude protein (CP) and gossypol content of CSM. The 23 week-old breeder cocks were fed the experimental diets for 15 weeks, euthanized and their testes removed for histological studies. The determined CP and gossypol contents of CSM were 35.11% and 570 g/ton respectively. The daily sperm production (DSP) by the breeder cocks was depressed when CSM dietary inclusion was above 50% with DSP values ranging from 1.509 to 2.909/mL. The investigation showed that replacing 75% SBM with CSM was not injurious to the non-reproductive health of the breeder cocks. However, CSM may not replace more than 50% of SBM for breeder cocks because of the depressing effect of gossypol on sperm production when this level is exceeded.